Partly processed meat products prepared for grilling as a source of protein. (September 2019) - Koricanac, V; Vranic, D; Petronijevic, R; Trbovic, D
Abstract: In the period January 2018 to December 2018, the levels of protein were measured in 864 samples of partly processed meat products prepared for grilling, from the Serbian market. Just 2.89% of these partly processed meat products contained protein content less then 14 g/100g, and so did not meet the requirement laid down in the national regulation. By groups, 97.89% of minced shaped meat, 98.71% of minced unshaped meat and 93.62% of fresh sausages met the requirement of national regulation. The meat product group with the biggest percentage of non-compliant meat products was the fresh sausages group – 6.38% of these contained less than the required protein content. All in all, most of the partly processed meat products met the national regulation regarding protein content. With average 16.23±1.82 g/100g of protein in raw, pre-thermal treatment samples, this group of meat products would be a good source of protein in human nutrition. Nonetheless, those meat products that did not meet national regulation requirements show that regular and periodic control of partly processed meat products is necessary and one of the most important steps in ensuring safe and quality meat products for consumers.